Divine Values in the Business Strategies of Private Companies: A Phenomenological Study of Charity and Zakat - Arfandi Arfandi; Alimuddin Alimuddin; Syarifuddin Syarifuddin (Vifada Management and Social Sciences, 2026)
Purpose: This study aims to understand the meaning and implementation of divine values in the business strategies of private companies through the practices of zakat and sadaqah at the Kalla Group. The study is motivated by the dominance of the conventional business paradigm, which tends to focus on profit maximization while neglecting spiritual dimensions and social justice. Research Design and Methodology: This study employs a qualitative approach, using interpretive phenomenology, to explore the subjective experiences of organizational actors in interpreting the concepts of Tawhid and Allah’s absolute ownership (Al-Milk al-Haqiqi) within corporate business management. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using data reduction, thematic classification, data presentation, and phenomenological interpretation. Findings and Discussion: The research findings indicate that zakat and charity are not only viewed as religious obligations but also serve as strategic instruments in fostering corporate blessings, moral responsibility, and social sustainability. The value of Tawhid promotes the development of a business orientation that is more ethical, humanistic, and focused on the common good. Implications: This study contributes to the development of a spiritual business paradigm and broadens the scope of phenomenological research in contemporary Islamic business.